2017
DOI: 10.2147/jvd.s103582
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of infrared thermography in the diagnosis of deep vein thrombosis: an evidence-based review

Abstract: Venous thromboembolism is a serious medical, social, and economic problem. A number of treatment options exist to decrease mortality and morbidity in patients with deep vein thrombosis (DVT). An accurate and timely diagnosis of this condition is important to improve immediate and long-term prognosis. The standard diagnostic algorithm implying assessment of the clinical probability of the disease, d-dimer test, and venous duplex ultrasound is not optimal. Infrared thermography is a relatively new diagnostic mod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 56 publications
0
4
0
Order By: Relevance
“…In the research work [16], using thermal imaging to find varicose validating the use of thermography in the diagnosis of a venous thrombosis, indicating the area where is seen more red because there is a higher temperature variation in those points. They also indicated that the varicose vein detection process took a period of 3 weeks to find out if varicose veins were seen in that area, thus ruling out recurrent muscle warmth in the legs.…”
Section: Resultsmentioning
confidence: 88%
“…In the research work [16], using thermal imaging to find varicose validating the use of thermography in the diagnosis of a venous thrombosis, indicating the area where is seen more red because there is a higher temperature variation in those points. They also indicated that the varicose vein detection process took a period of 3 weeks to find out if varicose veins were seen in that area, thus ruling out recurrent muscle warmth in the legs.…”
Section: Resultsmentioning
confidence: 88%
“…As far as we know, the detection of superficial vein phlebitis with IR thermography has not been described in literature before. Most medical applications of IR thermography focus on the detection of deep venous thrombosis, severe infection and non-invasive cancer detection [ 12 , 18 24 ]. These applications often examine thermal patterns of an affected limb and the interpretation is interpreter-dependent.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, there are number of studies used infrared thermography to screen existing medical conditions or progress of the disease, and evaluation of the effectiveness of treatment methods (20). For instance, thermography evaluation for coccygodynia after manipulative therapy (24), ankle sprains (25), open heart surgeries, reflex sympathetic dystrophy syndrome (RSD), and neurological conditions (26), deep vein thrombosis (27,28), soccer athletes injuries (29,30), muscle injuries (31), as a diagnostic evaluation and validation tool for osteopathic management in backpain (32), tendinopathy (33), gastrocnemius-soleus equinus (30), postoperative evaluation for total knee arthroplasty (34), hand-osteoarthritis (35), rheumatoid arthritis (36), juvenile rheumatoid Arthritis (37), knee-osteoarthritis (38), and for detecting the skin and breast cancer, burns, arthritis and skin allergic conditions (39).…”
Section: Introductionmentioning
confidence: 99%